Development of an LPS-based ELISA for diagnosis of Yersinia enterocolitica O:3 infections in Danish patients: a follow-up study - Dalby, Tine (BMC Microbiol, 2017)
BACKGROUND: The bacterium Yersinia enterocolitica causes gastroenteritis in humans. The study aimed to develop a diagnostic enzyme-linked immunosorbent assay (ELISA) for detection of Yersinia enterocolitica O:3 LPS antibodies in sera from Danish patients with suspected Yersinia enterocolitica O:3 gastrointestinal infection. As a part of this, antibody decay profiles after culture confirmed Yersinia enteritis were studied. RESULTS: An ELISA using Yersinia enterocolitica O:3 LPS as the coating antigen was developed for measuring IgA, IgG and IgM specific antibodies. A longitudinal collection of 220 sera drawn between 20 and 1053 days after onset of symptoms from 85 adult Danish patients with verified Yersinia enteritis were examined. A control group of 100 sera from healthy Danish blood-donors were analysed in order to determine the cut-off for interpretation of results. Serum samples from 62 out of 81 patients who delivered either the first or the second sample were found positive for specific antibodies against Yersinia enterocolitica O:3 LPS (77%). For samples collected within 60 days after onset of symptoms (n = 48) sensitivities of 58%, 42% and 79% for IgA, IgG and IgM antibodies were found. A sensitivity of 81% was found for these samples when using the definition of a positive result in either IgA, IgG or IgM as a combined positive. All samples received up to 36 days after onset of symptoms (n = 10) were found to be positive using this definition. For the period 61 to 90 days after onset of symptoms (n = 32), a combined sensitivity of 63% was found. The antibody levels as well as decay profiles for the three different immunoglobulin classes for the individual patients exhibited a large degree of variation. CONCLUSIONS: Using a definition of positive as a positive result for either IgA, IgG or IgM antibodies, a diagnostic sensitivity of 81% was achieved for samples received within 60 days after onset of symptoms. In particular, the levels of specific IgM antibodies were elevated. In comparison, the standard tube-agglutination assay achieved a sensitivity of 60% on the same samples. The sensitivity of the ELISA decreased the longer the duration of time since onset of symptoms. The ELISA was highly specific for Yersinia when testing sera from individuals with confirmed gastrointestinal infections by other bacteria. Moreover, the knowledge gained from this longitudinal study of antibody decay profiles can be used in future epidemiological studies of seroprevalence.